2009
DOI: 10.1126/scisignal.2000333
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Responses to Oxygen and Sugar Deficiency Allow Rice Seedlings to Tolerate Flooding

Abstract: Flooding is a widespread natural disaster that leads to oxygen (O(2)) and energy deficiency in terrestrial plants, thereby reducing their productivity. Rice is unusually tolerant to flooding, but the underlying mechanism for this tolerance has remained elusive. Here, we show that protein kinase CIPK15 [calcineurin B-like (CBL)-interacting protein kinase] plays a key role in O(2)-deficiency tolerance in rice. CIPK15 regulates the plant global energy and stress sensor SnRK1A (Snf1-related protein kinase 1) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
284
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(289 citation statements)
references
References 58 publications
4
284
0
1
Order By: Relevance
“…2 we put forward the hypothesis of a cross-talk between hypoxia and darkness signaling pathways for the induction of AlaAT expression. This hypothesis is consistent with the observation that in flooded rice, CIPK15 [calcineurin B-like (CBL)-interacting protein kinase] controls the expression of ADH as a response to low oxygen stress through SnRK1A (Lee et al 2009). …”
Section: Amino Acid Metabolismsupporting
confidence: 90%
See 2 more Smart Citations
“…2 we put forward the hypothesis of a cross-talk between hypoxia and darkness signaling pathways for the induction of AlaAT expression. This hypothesis is consistent with the observation that in flooded rice, CIPK15 [calcineurin B-like (CBL)-interacting protein kinase] controls the expression of ADH as a response to low oxygen stress through SnRK1A (Lee et al 2009). …”
Section: Amino Acid Metabolismsupporting
confidence: 90%
“…KIN10/KIN11 two members of the Snrk family were shown to mediate darkness and oxygen stress signal in Arabidopsis isolated mesophyll cells and whole plants (Baena-González et al 2007). CIPK15 was shown to act through Snrk1A for the regulation of sugar fermentation in anoxic rice (Lee et al 2009). Posttranslational regulation of GDC is triggered by hypoxia-induced increase in cytoplasmic (cyto) H + and Ca 2+ concentrations.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…One of mechanisms that underlie the anaerobic induction of type-2 genes would be transcriptional activation through specific cis-regulatory elements as seen in many anaerobic genes (Hoeren et al, 1998;Mohanty et al, 2012;Olive et al, 1991). Previous molecular characterization of rice knockout mutant for CIPK15 gene suggested that this protein may serve as a positive key regulator to direct the O 2 deficiency signal to sugar sensing cascade via activating SnRK1 (Lee et al, 2009). Therefore, the interference with sugar signaling by O 2 deprivation observed in type-1 and -2 genes may be mediated by this CIPK15-SnRK1 pathway.…”
Section: Figmentioning
confidence: 99%
“…AtSnAK1/GRIK2 and AtSnAK2/GRIK1 act as upstream kinases and activate SnRK1 (Hey et al, 2007;Shen et al, 2009). The calcineurin B-like-interacting protein kinase CIPK15 is an upstream regulator of SnRK1A in rice (Oryza sativa) and links oxygen-deficiency signals to the SnRK1-dependent sugar sensing cascade (Lu et al, 2007;Lee et al, 2009).…”
mentioning
confidence: 99%